Stress and Supportive Care Needs of Millennial Caregivers: A Qualitative Analysis. (March 2022) - Thomas Hebdon, Megan C.; Jones, Miranda; Neller, Sara; Kent-Marvick, Jacqueline; Thomas, Michael; Stewart, Elina; Aaron, Siobhan; Wilson, Christina; Peterson, Neil; Ellington, Lee
Millennial caregivers, born between 1981 and 1996, are an understudied caregiver group. They experience stress-related consequences of caregiving and are unique in their developmental stage and generational norms. The purpose of this study was to understand the context of caregiving and stressors for these caregivers. In total, 42 caregivers were recruited through Research Match and social media platforms. Caregivers completed online surveys with open-ended response questions and 15 caregivers completed semistructured interviews. Data were analyzed deductively and inductively using the Stress Process Model as a framework. Millennial caregivers described uncertainty and disruption as overarching experiences. Stressors related to balancing caregiving, work, and family responsibilities were most prominent. Caregivers reported needing support from friends/family, health care team members, community, and work/governmental policy. Mental health treatment was identified as most helpful for managing stress. Millennial caregivers have distinctive contexts that impact their caregiving needs. Caregiving interventions must take these needs into consideration.